Isoleucine at position 137 of haemagglutinin acts as a mammalian adaptation marker of H9N2 avian influenza virus - Weiwei Ma; Chenyang Ren; Lin Shi; Bo Meng; Yali Feng; Ying Zhang (Emerging Microbes and Infections)
The H9N2 subtype of avian influenza virus (AIV) is widely distributed among poultry and wild birds and is also a threat to humans. During AIV active surveillance in Liaoning province from 2015 to 2016, we identified 10 H9N2 strains exhibiting different lethality to chick embryos. Two representative strains, A/chicken/China/LN07/2016 (CKLN/07) and A/chicken/China/LN17/2016 (CKLN/17), with similar genomic background but different chick embryo lethality, were chosen to evaluate the molecular basis for this difference. A series of reassortants between CKLN/07 and CKLN/17 were generated and their chick embryo lethality was assessed. We found that the isoleucine (I) residue at position 137 (H3 numbering) in the haemagglutinin (HA) was responsible for the chick embryo lethality of the H9N2 virus. Further studies revealed that the threonine (T) to I mutation at HA position 137 enhanced viral replication in vitro and in vivo. Moreover, the HA-T137I substitution in H9N2 avian influenza virus increased the guinea pig transmission efficiency. We also found that the HA-T137I substitution was critical for α2,6-linked sialic acid binding preference and HA activation and stability of H9N2 virus. Our findings demonstrated that HA-137I is a key molecular marker for mammalian adaptation of H9N2 AIV.